Unveiling the Drivers of Enterprise Risk Management Disclosure: The Influence of Firm Complexity, BoD, and CRO - Nova Rachmania; Dewi Pangestuti (Politeknik Ganesha Medan, 2025)
This study aims to examine the influence of firm complexity, the board of directors, and the chief risk officer (CRO) on enterprise risk management (ERM) disclosure in energy sector companies listed on the Indonesian Stock Exchange (IDX) from 2018 to 2023. The sample for this study comprised 50 companies, selected using purposive sampling, and provide 300 data points. The research employed panel data regression analysis to assess the relationships between the variables. The findings reveal that while firm complexity and the composition of the board of directors do not significantly affect ERM disclosure, the presence of a chief risk officer has a positive and significant impact on the level of ERM disclosure. These results suggest that energy companies should prioritize the role of the chief risk officer in enhancing the transparency and quality of their ERM practices. Furthermore, to optimize ERM disclosure, companies must carefully evaluate their strategies regarding organizational complexity and the role of the board of directors. This study underscores the importance of having a dedicated risk management function and offers practical insights for energy sector firms seeking to improve their ERM frameworks in the context of corporate governance.